Development of Process Oriented Guided Inquiry Learning-based E-Module to Improve Critical Thinking Skill - Sri Septianti; Muzzazinah Muzzazinah; Meti Indrowati (Postgraduate, University of Mataram, 2022)
This study aims to determine the feasibility of a POGIL-based e-module to empower students' critical thinking skills. The type of research used is research and development with research procedures using ADDIE (Analysis, Design, Development Implementation, Evaluation) model development. This research is limited to the feasibility test of POGIL-based e-modules at the development stage. The assessment of the validity test results and the questionnaire practicality test were interpreted on a Likert scale. Based on data analysis, the following results were obtained: validity tests by POGIL-based e-module learning media obtained an average of 88.3% for media validity; 96.6% for the validity of the material; and 87.5% for Language validity. Practicality tests conducted by teachers get an average of 84% and students by 90.6%. Based on the validity and practicality test of POGIL-based e-module learning media to empower students' critical thinking skills, they are declared feasible to be used for further research